Travel Notes from the New Literacy Studies Instances of Practice - Pahl, Kate; Rowsell, Jennifer (New Perspectives on Language and Education, 2006)
This book joins two important fields, that of literacy and multimodality, with a focus on local and global literacies. Chapters include work on media, popular culture and literacy, weblogs, global and local crossings, in and out of educational settings in such locations as the US, the UK, South Africa, Australia and Canada